A Multifactorial Analysis of Communicative Performance Among Arabic Language Education Students - Fatwa Arifah; Puti Zulharby; Abeer Salaheldin Heider (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Communicative performance is a central goal of Arabic language education; yet, it is often unevenly achieved, despite students' positive attitudes toward the language. This study aims to reveal the relationship between language attitudes and Arabic communication performance; analyze the factors influencing the relationship between language attitudes and communication performance; and examine the implications for Arabic language learning. The qualitative research presented in this article is a continuation of the sequential explanatory Mixed-Methods design. Quantitative data were collected through a survey administered to 166 undergraduate students from Arabic Language Education programs at Universitas Negeri Jakarta and UIN Alauddin Makassar. The quantitative findings reveal a strong positive correlation between language attitudes and communicative performance (r = 0.650, p < 0.01). However, only 17.5% of students with high positive attitudes demonstrated high communicative performance. Qualitative analysis identified three factors related to the relationship between language attitudes and communication performance. 1) Individual factors, such as differences in educational background and gender. 2) pedagogical factors, such as learning methods, teaching materials, and learning evaluation techniques. 3) environmental factors, such as an Arabic-speaking environment and limited access to native speakers. The findings suggest that positive language attitudes alone are insufficient to produce effective communicative performance without the implementation of appropriate teaching strategies and adequate environmental support. The study recommends applying Communicative Language Teaching, restructuring the curriculum, fostering Arabic language communities, providing need-based learning materials, and adopting gender-responsive instructional approaches.